2019
DOI: 10.1371/journal.pone.0215875
|View full text |Cite
|
Sign up to set email alerts
|

Cephalometric studies of the mandible, its masticatory muscles and vasculature of growing Göttingen Minipigs—A comparative anatomical study to refine experimental mandibular surgery

Abstract: Over many decades, the Göttingen Minipig has been used as a large animal model in experimental surgical research of the mandible. Recently several authors have raised concerns over the use of the Göttingen Minipig in this research area, observing problems with post-operative wound healing and loosening implants. To reduce these complications during and after surgery and to improve animal welfare in mandibular surgery research, the present study elucidated how comparable the mandible of minipigs is to that of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 78 publications
1
8
0
Order By: Relevance
“…Minipigs are an established animal model for testing implants and bone repair material [26][27][28][29]. However, in 2019 a cephalometric study of the minipigs mandible revealed anatomical differences to the human mandible with potential complications in mandibular surgery research [30]. Our surgical procedures of tooth removal and implant insertion were similar to other studies [27,31].…”
Section: Discussionsupporting
confidence: 66%
“…Minipigs are an established animal model for testing implants and bone repair material [26][27][28][29]. However, in 2019 a cephalometric study of the minipigs mandible revealed anatomical differences to the human mandible with potential complications in mandibular surgery research [30]. Our surgical procedures of tooth removal and implant insertion were similar to other studies [27,31].…”
Section: Discussionsupporting
confidence: 66%
“…The bone remodeling rate, defined as the volume of bone turned over per unit volume of tissue per day, is 10% per month in pigs, compared with 3% per month in humans. [ 21–23 ] With these aspects in mind, interpretation of our findings in a human clinical setting demands cautiousness.…”
Section: Discussionmentioning
confidence: 99%
“…Afterward, the mandibular morphometry was performed by a single examiner and in duplicate using the Starrett® digital electronic caliper (capacity 0–150 mm; resolution 0.01 mm; and accuracy ± 0.02 mm). As recent information specific to this context is scarce regarding artiodactyl animals in general (Corte et al, 2019; Özkan et al, 2020; Paulo et al, 2020; Sundaram et al, 2019), much of the measurements adopted here were also based on and adapted from studies with specimens from the order Carnivora (Barroso et al, 2009; Igado, 2014; Magalhães, Ferreira Júnior, et al, 2019; Magalhães, Romão, et al, 2019; Maximiano Neto et al, 2020; Souza Junior et al, 2013, 2016).…”
Section: Methodsmentioning
confidence: 99%